(untitled) (Research, Society and Development, 2022)
COVID-19 is a highly contagious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) becoming a major threat worldwide due to its fast-spreading nature and more aggressive variants, such as the case of Omicron. The main interaction structure of the virus with the host cell is the spike region of the Spike protein called RBD, a structure that has had several mutations, making the search for drugs difficult. Based on this scenario, the present work aimed to evaluate the profile of interactions between molecules of natural origin against the RBD region of the Spike (S) protein of SARS-CoV-2, Ômicron variant. In the first methodological step, there was a molecular modeling of the RBD structure of a sequence obtained in Brazil and tests for its characterization and structural validation. Then, molecular docking was performed between 6 phytochemical ligands: Curcumin, Carvacrol (±)-Limonene, Glycyrrhizin, Allicin and Quercetin-3-Arabinoside in the specific region modeled RBD, after obtaining the best results, the complexes formed were evaluated by RMSD and RMSF. In the homology of the RBD region, a structure with low structural errors was obtained. In the interactions of each phytochemical, the molecules glycyrrhizin and quercetin showed higher molecular affinity, binding to the active site found in RBD. Molecular dynamics confirmed the interaction of ligands and the stability of the complexes during the simulations. Quercetin and glycyrrhizin showed a potential molecule binding to the RBD region of protein S, from the genome of the unprecedented omicron variant of SARS-CoV-2 sequenced in Brazil.